2002
DOI: 10.1291/hypres.25.343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signicance of Blood Pressure Response Triggered by a Doctor's Visit in Patients with Essential Hypertension.

Abstract: The clinical significance of the pressor response triggered by blood pressure measurement, the so-called "white-coat effect," was studied in relation to left ventricular structure and function in patients with essential hypertension. We studied 75 consecutive, never-before treated patients with essential hypertension (54 2 (SE) years; 31 men). Beat-to-beat blood pressure (Finapres) was monitored at rest, during conventional blood pressure measurement by a doctor, and during a mental stress test physicians must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…First, we adopted only one value measured within 1 month before or after the period of home blood pressure measurement as casual blood pressure, since almost subjects were healthy normotensives. Therefore, the influence of the white-coat effect may have been strong (22), and there is a possibility that some whitecoat hypertensives were included in the nontreated hypertensive group. Second, we took three home blood pressure measurements on each occasion in this study.…”
Section: Discussionmentioning
confidence: 99%
“…First, we adopted only one value measured within 1 month before or after the period of home blood pressure measurement as casual blood pressure, since almost subjects were healthy normotensives. Therefore, the influence of the white-coat effect may have been strong (22), and there is a possibility that some whitecoat hypertensives were included in the nontreated hypertensive group. Second, we took three home blood pressure measurements on each occasion in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although Lantelme et al (22) found a weak correlation between the two WCE measures (r= 0.31, p= 0.004), Palatini et al found none (26). Munakata et al found that the true WCE, measured with a Finapres device, correlated with left ventricular mass index in men, but not in women (27), but Lantelme et al (22) found no relationship in either sex. Palatini et al (26) found a significant correlation between the true WCE and the blood pressure response to a speech task (r= 0.50, p< 0.001).…”
Section: Reduced Clinic Pressurementioning
confidence: 98%
“…Another possible explanation is a gender difference in pressor response to psychological stress. We have previously reported in untreated hypertensive patients that men showed a significantly greater blood pressure increase in response to experimental psychological stress than did women 13) . Our study has several limitations.…”
Section: Discussionmentioning
confidence: 79%